2012
DOI: 10.1105/tpc.112.103002
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Chloroplast RNA Binding Proteins CP31A and CP29A Associate with Large Transcript Pools and Confer Cold Stress Tolerance by Influencing Multiple Chloroplast RNA Processing Steps

Abstract: Chloroplast RNA metabolism is mediated by a multitude of nuclear encoded factors, many of which are highly specific for individual RNA processing events. In addition, a family of chloroplast ribonucleoproteins (cpRNPs) has been suspected to regulate larger sets of chloroplast transcripts. This together with their propensity for posttranslational modifications in response to external cues suggested a potential role of cpRNPs in the signal-dependent coregulation of chloroplast genes. We show here on a transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
172
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(182 citation statements)
references
References 58 publications
8
172
0
Order By: Relevance
“…If we had chosen bulk sequencing to assay the editing extent in the orrm1 mutant plant, there would not have seen any detectable edited peak for the 12 sites whose editing extent in the orrm1 mutant is < 0.1 (Table S1). Recently, Kupsch et al (44) found that CP31A associates with large transcript pools and confers cold stress tolerance by influencing multiple chloroplast RNA processing events (44). The authors indicate that relative to its effect on RNA stability, the effect of CP31A on editing extent is minor.…”
Section: Discussionmentioning
confidence: 99%
“…If we had chosen bulk sequencing to assay the editing extent in the orrm1 mutant plant, there would not have seen any detectable edited peak for the 12 sites whose editing extent in the orrm1 mutant is < 0.1 (Table S1). Recently, Kupsch et al (44) found that CP31A associates with large transcript pools and confers cold stress tolerance by influencing multiple chloroplast RNA processing events (44). The authors indicate that relative to its effect on RNA stability, the effect of CP31A on editing extent is minor.…”
Section: Discussionmentioning
confidence: 99%
“…One includes the proteins that bind a large set of chloroplast RNAs with little gene specificity, such as the cpRNP proteins that intervene at multiples steps of gene expression (Kupsch et al, 2012). The other consists of the proteins that bind to a restricted subset of plastid transcripts or to a single one and have more specific roles.…”
Section: Mac1 Is Phosphorylated To Different Extents Depending On Gromentioning
confidence: 99%
“…Chloroplasts from 5-week-old Arabidopsis plants were prepared as described by Kupsch et al (2012). Stroma was separated from membranes by centrifugation at 40,000g for 10 min.…”
Section: Protein Isolation Western Blotting and Rip-chip Analysesmentioning
confidence: 99%
“…Stroma was separated from membranes by centrifugation at 40,000g for 10 min. Membranes were washed twice, and equal volumes of total chloroplasts, stroma, and membranes were loaded onto an SDS-PAGE system and investigated by western blot as described (Kupsch et al, 2012).…”
Section: Protein Isolation Western Blotting and Rip-chip Analysesmentioning
confidence: 99%